A facile strategy to fabricate fluorescent polymeric nanoparticles with aggregation-induced emission feature via oxygen-tolerated light-induced living polymerization. (August 2021) - Yu, Shengxian; Yan, Wenfeng; Long, Wei; Yuan, Yiyang; Ouyang, Hui; He, Ziyang; Tian, Jianwen; Liu, Meiying; Zhang, Xiaoyong; Wei, Yen
Abstract: Aggregation-induced emission (AIE) materials have attracted more and more attention for their broad applications in cell imaging, fluorescent detection, photodynamic therapy and so on. Obvious different from traditional fluorescence quenching materials, AIE-active materials could emit stronger fluorescence in concentrated and solid state. In this work, an AIE-active molecule (named as TPE-DB) was synthesized and applied to prepare amphiphilic fluorescent copolymers through light-induced RAFT polymerization in the present of air. The poly(ethylene oxide) monomethacrylate (PEGMA), itaconic acid (IA) and TPE-DB were selected as monomers and Ir 3+ complex was used as photoredox catalyst. The samples were carefully characterized and analyzed by different techniques. More interesting, we demonstrated that TPE-PEGMA-IA could form nanoparticles with small size and high water dispersibility. The results from cell viability evaluation and confocal laser scanning microscopy imaging suggested that these fluorescent nanoparticles possess low cytotoxicity and are promising for biological imaging. Owing to the introduction of IA, these fluorescent polymeric nanoparticles (FPNs) could also be utilized for drug delivery. Taken together, we believe that the light-induced polymerization should be a simple and useful route for synthesizing AIE-active fluorescent copolymers, which could greatly advance the biomedical applications of AIE-active functional materials. Highlights: Fabrication of fluorescent polymeric nanoparticles (FPNs) with AIE feature. Light-induced RAFT polymerization was used to prepare the FPNs. The light-induced RAFT polymerization is oxygen tolerant. The AIE-active FPNs are potential for other biomedical applications.